The confidence factor: Self-efficacy’s impact on K-pop fans’ engagement and identity on social media - Roslan, Muhammad Amirul Asyraaf; Azmi Murad, Masrah Azrifah; Nasharuddin, Nurul Amelina (Elsevier B.V., 2025)
This study explores the impact of Self-efficacy (SE) on the Behavioural Intention (BI) to use Social Media (SM) among K-pop fans on X (formerly known as Twitter). Drawing from the Technology Acceptance Model and SE Theory, the research investigates how confidence in SM skills influences fan engagement, content creation, community involvement, and participation in fandom activities. The study combines both quantitative and qualitative approaches, with 25 public K-pop fan accounts observed over a four-week period. Quantitative data were collected through a scoring system across key categories—content creation, community engagement, campaign participation, and technical proficiency—while qualitative insights were gathered from the researcher’s observations. Results indicate that high SE is associated with active participation in content creation, leadership in fandom campaigns, and proficient use of platform features. In contrast, low SE fans engage minimally, often limiting themselves to passive actions. The study discusses how SE empowers fans to take on leadership roles within the fandom and create a sense of community through increased engagement. Limitations include the reliance on public accounts and the subjectivity of researcher-based observations. Recommendations include fostering SE through training or mentorship programs to enhance fan participation and community cohesion. This study contributes to understanding the psychological factors that shape SM engagement in fandoms.